Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.15406/jamb.2021.10.00318
|View full text |Cite
|
Sign up to set email alerts
|

Short term temperature fluctuations affect embryonic and larval development of yellow perch (Perca flavescens)

Abstract: Early life stages of fishes are critical stages due to their importance in enhancing recruitment. Given the high mortality through the embryonic and larval stages, managers have started investigating factors that impact these stages. Environmental factors, such as water temperature, have been found to play a larger role in early life survival. Climate change predications will be more apparent in northern temperate systems like the Great Lakes. Yellow perch Perca flavescens are an important sport fish in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…However, they did find a change with net confinement stress at one-week post-hatch depicting, the HPI axis begins to be prevalent at this life stage (Jentoft et al, 2002). Another study that introduced cold shock on yellow perch embryos, found it to account for less mortality that the steady temperature treatment (Sepulveda Villet, 2021). Another notable study conducted on yellow perch in response to handling and salinity stress found that handling at 20°C might result in lesser activation of the stress response, whereas plasma cortisol was elevated in the 14°C and 26°C treatments with handling stress; In the normal condition, 14°C had the least amount of plasma cortisol.…”
Section: Perch and Stressmentioning
confidence: 95%
“…However, they did find a change with net confinement stress at one-week post-hatch depicting, the HPI axis begins to be prevalent at this life stage (Jentoft et al, 2002). Another study that introduced cold shock on yellow perch embryos, found it to account for less mortality that the steady temperature treatment (Sepulveda Villet, 2021). Another notable study conducted on yellow perch in response to handling and salinity stress found that handling at 20°C might result in lesser activation of the stress response, whereas plasma cortisol was elevated in the 14°C and 26°C treatments with handling stress; In the normal condition, 14°C had the least amount of plasma cortisol.…”
Section: Perch and Stressmentioning
confidence: 95%